Using Mobile Phones Through the Flipped Classroom in High School Geography Course - Domínguez Herrera, Eduardo; Rebeles Martínez, Ana Gabriela (Boletín de Estudios Geográficos, 2024)
The general objective of this mixed study is to analyze the use of mobile phones outside the classroom during Unit 1 “Changing and dynamic society” of the geography course, integrating the flipped classroom model. The results of this research indicate that the use of mobile phones positively influences the autonomy and enthusiasm of students. In addition, various benefits are evident in the teaching-learning process of Geography, such as improved communication, searching for information, conducting research, understanding school subjects, resolving doubts, obtaining new information and easy access to web pages. In conclusion, mobile phones are technological devices that support the teaching-learning process on geography. In addition, the flexibility of time and space of these devices encourages personalized learning through the consultation and use of school content.